Creutzfeldt-Jakob Disease in the United States, 1979-1994: Using National Mortality Data to Assess the Possible Occurrence of Variant Cases - Robert C. Holman; Ali S. Khan; Ermias D. Belay; Lawrence B. Schonberger (Emerging Infectious Diseases, 1996)
After a cluster of Creutzfeldt-Jakob disease (CJD) cases among unusually young patients was reported recently from the United Kingdom, we examined trends and the current incidence of CJD in the United States. We found that the age-adjusted CJD death rate in the United States is similar to published estimates of the crude incidence of CJD worldwide and has continued to be stable from 1979 through 1994. The number of CJD deaths in persons <45 years of age remained stable during this period. We found no evidence of the variant form of CJD.